Thermal conductivity of carbon nanotube nanofluid—experimental and theoretical study - Walvekar, Rashmi Gangasa; Ismail, Ahmad Faris; Khalid, Mohammad (Wiley-BLACKWELL, 2012)
In this work, thermal conductivity of carbon nanotubes' (CNTs) nanofluid is studied both experimentally and theoretically. CNT nanofluids were stabilized using gum arabic (GA). The concentration of CNTs was varied from 0.01–0.1 wt% while the concentration of GA was varied from 1–2.5 wt%, respectively. The effect of particle volume fraction and temperature on the thermal conductivity enhancement of the nanofluids was also studied. A simple thermal conductivity model which demonstrates the effect of diameter and aspect ratio of the CNTs and takes into account the effect of temperature on thermal conductivity enhancement is presented. Good agreement between experimental and estimated values proves that the proposed model can provide precise prediction of the thermal conductivity of fluid containing CNTs.